Nb/NiTi laminate composite with high pseudoelastic energy dissipation capacity. (August 2022) - Cai, J.; Mao, S.; Liu, Y.; Cui, L.; Zhang, J.; Zhang, Z.; Han, X.
Abstract: NiTi shape memory alloys (SMAs) with marked hysteresis between the forward and reverse martensitic transformations are attractive for the applications in passive damping. However, the stress hysteresis of NiTi SMAs is usually 150–300 MPa, limiting their energy dissipation to ∼10 MJ/m 3 . Here, we designed a bulk Nb/NiTi laminate composite with a reversible energy dissipation capacity of ∼30 MJ/m 3 and a plateau strength of ∼750 MPa, which are outstanding among the common bulk energy dissipation materials. This high performance is attributed to the strong interaction between the pseudoelastic NiTi and the non-pseudoelastic Nb lamellae within the composite. The intrinsically plastic Nb layers deform in a pseudo-super elastic manner, involving elastic lattice deformation, reversible motion of dislocations, and reversed plastic deformation. These are enabled by the unique phenomenon of lattice strain matching the martensitic transforming. This study offers a new pathway for the design of high energy dissipated bulk materials. Graphical abstract: Image 1 Highlights: NiTi based shape memory alloys and composites exhibit a high damping capacity with their hysteretic pseudoelastic behavior. The ex situ composites prepared by accumulative roll-bonding are not restricted to the eutectic volume fraction of the second phase, thus allowing flexibility and the option to fine tune for the optimal microstructure for the best performance. The components in NiTi matrix composites have a strong interaction during their deformation. A recoverable motion of dislocations arose in the plastic components constrained by NiTi shape memory alloy in NiTi matrix composites.